The mechanism of Renshen-Fuzi herb pair for treating heart failure—Integrating a cardiovascular pharmacological assessment with serum metabolomics - Chen, Xiaofei; Chen, Yulong; Xie, Shiyang; Wang, Xiaoyan; Wu, Yali; Zhang, Hui; Zhao, Ya; Jia, Jinhao; Wang, Bin; Li, Weixia; Tang, Jinfa; Xiao, Xiaohe (Frontiers in Pharmacology, 2022)
Background: Renshen-Fuzi herb pair (RS-FZ) is often used in the clinical treatment of heart failure (HF) and has a remarkable therapeutic effect. However, the mechanism of RS-FZ for treating HF remains unclear. In our study, we explored the mechanism of RS-FZ for treating HF. Methods: Evaluation of RS-FZ efficacy by cardiovascular pharmacology. Moreover, Global metabolomics profiling of the serum was detected by UPLC-QTOF/MS. Multivariate statistics analyzed the speciﬁc serum metabolites and corresponding metabolic pathways. Combining serum metabolomics with network pharmacology, animal experiments screened and validated the critical targets of RS-FZ intervention in HF. Results: RS-FZ significantly ameliorated myocardial fibrosis, enhanced cardiac function, and reduced the serum HF marker (brain natriuretic peptide) level in rats with HF. Through topological analysis of the “Metabolite-Target-Component” interaction network, we found that 79 compounds of RS-FZ directly regulated the downstream specific serum metabolites by acting on four critical target proteins (CYP2D6, EPHX2, MAOB, and ENPP2). The immunohistochemistry results showed that RS-FZ observably improved the expression of CYP2D6 and ENPP2 proteins while decreasing the expression of EPHX2 and MAOB proteins dramatically. Conclusion: The integrated cardiovascular pharmacological assessment with serum metabolomics revealed that RS-FZ plays a crucial role in the treatment of HF by intervening in CYP2D6, EPHX2, MAOB, and ENPP2 target proteins. It provides a theoretical basis for RS-FZ for treating HF.